Giant trouble - Vernon, Ursula (Vernon, Ursula. Hamster princess, 2017)
"When Princess Harriet climbs an enormous beanstalk, she finds an even bigger surprise--a giant rabbit is keeping a goose and a girl who is half-harp-half-hamster as prisoner, and it's up to Harriet to save the day"--